Comparison of Energy Contributions and Workloads in Male and Female Badminton Players During Games Versus Repetitive Practices - Fu, Yue; Liu, Yu; Chen, Xiaoping; Li, Yongming; Li, Bo; Wang, Xinxin; Shu, Yang; Shang, Lei (Frontiers in Physiology, 2021)
Purpose: The aim of this study was to compare the energy contributions and workloads in men and women during badminton matches versus frequently used multi-ball smash practices. Methods: 14 badminton players performed one badminton singles game and one session of smashing practice on separate days. The energy contributions were examined in terms of each individual’s three energy systems and substrate oxidation, while workloads included heart rate (HR), Player Load, accelerations, decelerations, changes of direction and jumps. Results: (1) During games, male players exhibited higher adenosine triphosphate-phosphocreatine system contribution (EPCr, kJ) (p=0.008) and average rate of carbohydrate oxidation (RCHO, g/min) (p=0.044) than female players, while female players showed greater absolute Player Load (p=0.029) and more accelerations (p=0.005) than male players. Furthermore, players who lost performed higher relative Player Load (p=0.017) than those who won. (2) Higher energy system contributions, including EPCr (kJ) (p=0.028), EHLa (kJ) (p=0.024), EAer (kJ) (p=0.012), ETot (kJ) (p=0.007) and RCHO (g/min) (p=0.0002), were seen in male players during repetitive spike practices. Male players also made greater number of jumps (p=0.0002). (3) Players exhibited higher aerobic energy contribution (p＜0.001), mean HR (p=0.002) and HRmax(p=0.029) during games, while exhibiting greater anaerobic energy contribution (p＜0.001) and relative Player Load (p=0.001) during repetitive practices. Conclusions: The similarities between male and female badminton players in proportional use of the three energy systems during games and repetitive spike training indicate similar relative energy demands for both genders. However, considering the need for higher aerobic capacity in competition, it might be advisable to design appropriate work: rest ratios for repetitive practices in daily training.